Applying Internet of things and blockchain in smart cities industry and healthcare perspectives - Abhishek, Kumar; Chakraborty, Chinmay 1984- (IGI Global, 2024)
The convergence of Internet of Things (IoT) technology and blockchain offers transformative potential for the development of smart cities, enhancing industry operations and healthcare systems. IoT devices generate vast amounts of data to optimize urban infrastructure and improve service delivery, while blockchain provides a secure, transparent framework for managing data. Across industries, this collaboration leads to smarter manufacturing processes and efficient logistics. In healthcare, it enhances patient care through secure data sharing and streamlined administrative processes. A concerted effort to address these technical, regulatory, and ethical challenges is crucial for effective and responsible integration of IoT and blockchain in smart cities for improved urban living and healthcare services. Applying Internet of Things and Blockchain in Smart Cities: Industry and Healthcare Perspectives explores the application of IoT and blockchain technology for smart city integration in healthcare industries and business processes. It offers solutions for this effective convergence, through aspects like cloud and digital technology, or security and privacy practices. This book covers topics such as machine learning, energy management, and wearable devices, and is a useful resource for business owners, computer engineers, agriculturalists, security professionals, healthcare workers, academicians, researchers, and scientists.
Keywords: Blockchains (Databases) -- Medical applications; Computer networks -- Security measures; Data privacy; Data protection; Internet of things -- Medical applications; Medical informatics -- Security measures; Smart cities -- Security measures